2021
DOI: 10.1245/s10434-021-10026-w
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dispositional Optimism Predicts Better Health-Related Quality of Life After Esophageal Cancer Surgery: A Nationwide Population-Based Longitudinal Study

Abstract: Purpose To assess whether higher dispositional optimism could predict better health-related quality of life (HRQL) after esophageal cancer surgery. Methods This Swedish nationwide longitudinal study included 192 patients who underwent esophagectomy for cancer. The exposure was dispositional optimism measured by the Life Orientation Test-Revised (LOT-R) at 1 year post-surgery. Patients were categorized into four subgroups (very low, moderately low, moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In addition, more optimistic people are less likely to develop psychological comorbidities and feel lonely [31,42], which may decrease the risks of mortality [8,43]. Moreover, higher dispositional optimism predicts better health-related quality of life [44], and the latter further predicts better survival after esophageal cancer surgery [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more optimistic people are less likely to develop psychological comorbidities and feel lonely [31,42], which may decrease the risks of mortality [8,43]. Moreover, higher dispositional optimism predicts better health-related quality of life [44], and the latter further predicts better survival after esophageal cancer surgery [45].…”
Section: Discussionmentioning
confidence: 99%
“…Data for this longitudinal study is from a prospective, ongoing Swedish-nationwide cohort study entitled Oesophageal Surgery on Cancer patients—Adaptation and Recovery (OSCAR). Detailed description of the OSCAR study can be found elsewhere [ 16 , 17 ]. In brief, it includes patients undergoing esophagectomy for cancer in Sweden from January 1, 2013 and onwards.…”
Section: Methodsmentioning
confidence: 99%
“…Optimism is a personality trait that remains relatively stable over time [62] and has been shown to be protective in a broad range of contexts [63]. Higher dispositional optimism predicted higher health-related quality of life after surgery in patients with oesophageal cancer [64]. A significant association was seen between optimism and pain experience [65], and fatigue in patients with myocardial infarction [66], with subjectively and objectively reported physical health outcomes and higher effect size for the self-ratings [63].…”
Section: Dispositional Optimismmentioning
confidence: 99%
“…Higher levels of optimism correlated with lower levels of depression and anxiety [68]. The association and predictive strength of optimism within several areas are well established but further research is needed to investigate underlying pathways for causality [63,64,72].…”
Section: Dispositional Optimismmentioning
confidence: 99%